Motivations for entrepreneurship - Ang, Alina Jin Eng (2008)
This research desires to present a framework encompassing both macro and micro (environmental and personality factors) views that will enable our readers to have a simple yet holistic understanding on the factors that cause an individual to become an entrepreneur, and concurrently presenting the inter-play between the factors.